2012
DOI: 10.4161/epi.20236
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell global methylation and IL-6 promoter methylation in association with diet and lifestyle risk factors in a cancer-free population

Abstract: Keywords: DNA methylation, diet, lifestyle factors, cancer As aberrant DNA methylation is associated with cancer and other human diseases, there are growing interests in determining how environmental exposures may affect patterns of DNA methylation. Previous studies found older monozygotic twins were more diverse in DNA methylation patterns than were younger monozygotic twins.17 There is also evidence that DNA methylation patterns in individuals change over time, 18 supporting aging and/or external environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 47 publications
6
83
2
1
Order By: Relevance
“…29,31 Little is known about the association between variation in one-carbon metabolism genes and genome-wide methylation. Further, while there is evidence that dietary folate intake may be associated with genome-wide methylation in WBCs, [32][33][34] it remains to be elucidated whether an association also exists for methylation levels in breast tissues with folate concentrations in the breast.…”
Section: Introductionmentioning
confidence: 99%
“…29,31 Little is known about the association between variation in one-carbon metabolism genes and genome-wide methylation. Further, while there is evidence that dietary folate intake may be associated with genome-wide methylation in WBCs, [32][33][34] it remains to be elucidated whether an association also exists for methylation levels in breast tissues with folate concentrations in the breast.…”
Section: Introductionmentioning
confidence: 99%
“…All of the studies used BMI or changes in BMI to classify obesity, and two studies also used percentage body fat 32 33 . The majority of these investigations, including a large study combining four study populations, including up to 1254 individuals 34 , did not find an association between obesity and global methylation 33,[35][36][37][38][39][40] . Two studies that included only women 32 41 , found reduced global methylation with increasing BMI, however in one of these studies this only occurred in the presence of low concentrations of the methyl donor folate 32 .…”
Section: Global Methylation and Obesitymentioning
confidence: 99%
“…A recent microarray-based study found that approximately 39% of CpG sites analyzed were differentially methylated between leukocyte subgroups (91). However, a recent report did not find any association between L1 methylation and blood cell count (115). Another potential caveat for all cancer biomarker studies is tumor subtype heterogeneity, where the biomarker under investigation is a feature of only 1 disease subtype.…”
Section: Other Considerations For Epigenetic Risk Studiesmentioning
confidence: 99%